Quantification of superficial growth and the pigmentation of filamentous fungi by effect of oscillating magnetic field. - Anaya Villalpanda, Matilde; Borrego Alfonso, Sofía F.; Barbará Morales, Eduardo (Revista CENIC Ciencias Biológicas)
This work was to quantify the superficial growth and the pigmentation of filamentous fungi colonies by effect of an extremely low frequency oscillating magnetic field (OMF-ELF) depending on nutritional status of these microorganisms in two culture media. OMF-ELF of 2 mT by 60 Hz/200 V during 2 h (optimization of an experimental design) was applied at two filamentous fungi strains isolated from indoor environments: Aspergillus niger (hyaline mycelium seen under the optic microscope) and Cladosporium cladosporioides (pigmented mycelium), this latter strain was used as a negative control. The strains were inoculated in Petri dishes with Malt Extract Agar (MEA) and Czapek Dox Agar (CDA), incubated at 30°C and photographs were taken every 4 hours for 10 days. The area (superficial growth) and color intensity (pigmentation) of these colonies were evaluated by digital images processing (DIP) using MatLab®. The stimulating effect of OMF-ELF on the cellular metabolism of both fungal strains was demonstrated, with an increase of the superficial growth and a greater variation in pigmentation (indicative of sporulation by conidiogenesis) in CDA until reaching values of spores similar to when there are enough nutrients (MEA). The predictive mathematical model obtained by optimization of the experimental design to predict the growth of Aspergillus niger colony was validated with the algorithm implemented for the DIP. It was concluded that the OMF-ELF stimulated the metabolism of the studied fungal strains independently of the nutrients in the culture media and that the DIP is a precise technique to quantify the macroscopic phenomena that occur due to magnetobiological effects at the cellular level.